2009
DOI: 10.1111/j.1749-6632.2008.03985.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Inflammation, and Cognitive Function

Abstract: Inflammation, particularly low-grade chronic inflammation, appears to affect several brain functions, from early brain development to the development of neurodegenerative disorders and perhaps some psychiatric diseases. On the other hand, nutrition and dietary components and patterns have a plethora of anti- and pro-inflammatory effects that could be linked to cognitive function. Even a modest effect of nutrition on cognitive decline could have significant implications for public health. This paper summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 127 publications
1
82
0
4
Order By: Relevance
“…Other inflammatory mediators have also been linked to cognitive dysfunction, including interleukin (IL)-6, IL-1b, tumour necrosis factor-a and a 1 -antichymotrypsin [12,13]. However, these studies suggest an association rather than a causal link [14].…”
Section: Mechanisms Of Cognitive Impairmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Other inflammatory mediators have also been linked to cognitive dysfunction, including interleukin (IL)-6, IL-1b, tumour necrosis factor-a and a 1 -antichymotrypsin [12,13]. However, these studies suggest an association rather than a causal link [14].…”
Section: Mechanisms Of Cognitive Impairmentmentioning
confidence: 86%
“…Depressive symptoms are present in elderly people with cognitive impairment or dementia [80], but, while it is associated with impairment in executive function, memory and processing speed, it may account for only 1-2% of the variance in cognition in COPD [8,12]. In the NOTT trial the modest improvement in cognitive function was not associated with improvement in emotional or depressive symptoms [8].…”
Section: Depressionmentioning
confidence: 99%
“…One study found that levels of interleukins 1β (IL1β) correlated with adiposity and cognitive impairment (Erion et al, 2014). Inflammation, particularly chronic low-grade inflammation seems to affect several brain functions, from the early development of the brain to the development of neurodegenerative and psychiatric diseases, associated with cognitive deficits and dementia (Wärnberg, Gomez-Martinez, Romeo, Diaz, & Marcos, 2009). Another hypothesis focuses on the factors involved in arteriosclerosis and vascular factors involved in dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Further covariates were selected based on the impact on cognition and inflammation in our sample as well as the current literature describing their effects on inflammation or cognitive function, such as depression, cardiovascular factors, metabolic factors and APOE genotype [36,37,38,39,40,41]. Depression was assessed by the 15-item Geriatric Depression Scale [42], which has been shown to be valid and to have excellent test/re-test reliability [43].…”
Section: Methodsmentioning
confidence: 99%